Superparamagnetic Manganese Ferrite and Strontium Bioactive Glass Nanocomposites: Enhanced Biocompatibility and Antimicrobial Properties for Hyperthermia Application - Tripathi H.; Pandey G.C.; Dubey A.; Shaw S.K.; Prasad N.K.; Singh S.P.; Rath C. (My University, 2025)
Herein, the strontium bioactive glass with ferrite composites is studied for the application of biocompatibility and magnetic hyperthermia. The bioactive glass SrBG (46.1SiO2–21.9CaO–24.4Na2O–2.6P2O5–5SrO) prepared by the melt quench technique at 1400 °C and manganese ferrite (MnFe2O4) prepared by the modified microwave reflux oven are mixed together and sintered at 400 °C for 6 h for making composites. The in vitro bioactivity of these composites is observed by immersing in simulated body fluid (SBF). The growth of the precipitated hydroxyapatite phase observed after SBF treatment is confirmed by the X-ray diffractometer (XRD), Fourier transform infrared (FTIR) spectrometer, and scanning electron microscope (SEM) results. The in vitro cell viability assessment of these composites with MG-63 cell lines indicates that the composites are biocompatible in nature. Furthermore, these composites show the antibacterial effect on the E. coli and S. Aureus bacteria cells. The room temperature superparamagnetic behavior accompanied by the heating ability in these composites proves their potential role for hyperthermia applications. © 2020 Wiley-VCH GmbH